Contested social relations in the platform economy: Class structurisation and collectivisation in ride-hailing services in India. (1st January 2021) - Sharma, Padmini
Abstract : The development of platform capitalism is restructuring social relations across the globe by altering traditional hierarchical structures, internal labour relations and their micro-political interactions. Digitally mediated platforms appear to be changing relational dynamics, contributing to a growth in individualisation among the workers. The platform economy, in general, and ride-hailing services, in particular, represent an emerging capitalistic regime that is breeding a working class with often contradictory class locations and class positions. Because the class dimension in the existing literature concerning platform workers in India has been less critically approached, this research intends to use class-based theorisation to analyse capital–labour relations in the ride-hailing service, with the aim of reflecting on the linkages between class location, class consciousness and class practices among the workers. This article highlights how the internal contradictions, combined with the external structural factors, lead to growing instrumental collectivism among the platform working class that falls short of challenging the capitalistic platform regime.